The Importance of Personal Financial Management for Students of Islamic Economics Study Program STAIN Bengkalis - Juanita, Vivi; Hakim, Imam (STAIN Bengkalis, 2022)
This research aims to discuss the importance of personal financial management for students. This study aimed to determine the level of financial management and the effect of gender, age, and expenditure partially or simultaneously on student financial management. This type of research is a survey—sampling random sampling. Data was obtained by distributing questionnaires to 43 respondents. The data analysis technique used is multiple linear analysis. The results showed that the level of financial management indicated that the financial management level of students of the Islamic Economics Study Program STAIN Bengkalis was in the high category, namely 80.5%, where aspects that are in the middle class are aspects of financial use 78% and aspects of recording 78%. Aspects of the high category, namely financial planning 85.5% and storage 79.5% here, it can be seen that students of the Islamic Economics Study Program STAIN Bengkalis realize the importance of financial management. Gender affects the financial management of Islamic Economics Study Program students at STAIN Bengkalis. Age does not affect students' financial management of the Islamic Economics Study Program STAIN Bengkalis. Expenditures do not affect students' financial management of the Islamic Economics Study Program STAIN Bengkalis. Gender, age, and payment simultaneously affect students' financial management of the Islamic Economics Study Program STAIN Bengkalis.